Proposing a Functional Orthography for Lhowa: Issues, Challenges and Strategies - Regmi, Ambika; Regmi, Dan Raj (Nepalese Linguistics, 2025)
This paper proposes a functional and pedagogically easing orthography for Lhowa, a preliterate Tibeto-Burman language of Nepal. Both Devanagari and Tibetan Lama scripts proposed in the past, with a little understanding of phonological, cultural and pedagogical factors, have not yet been fully accepted and satisfactorily employed in writing. Holding up transformative worldview, this study has employed qualitative research design in collecting and analyzing data on major issues and challenges of orthography development and suggesting practical strategies to meet those challenges. The findings reveal a tension between maintaining the socio-cultural identity and easing educational efforts in the choice of orthography for languages like Lhowa in Nepal. Indeed, Tibetan Lama script may better support cultural identity of Lhowa than Devanagari script; however, literacy goals are more effectively achieved by adapting the latter. Such orthography is indispensable for literacy and multilingual education for the empowerment of the speech community like Lhowa in Nepal.